Improvement of Chlorophyll, Antioxidant Properties, and Biomass Yield in Sweet Basil (Ocimum basilicum L.) Using Chitosan at Various Growing Stages - Qazizadah, Ahmad Zubair; Nakasha, Jaafar Juju; Sinniah, Uma Rani; Wahab, Puteri Edaroyati Megat (Department of Agronomy and Horticulture, IPB University, 2026)
Sweet basil (Ocimum basilicum L.) is known for its numerous health-promising antioxidant phytochemicals and is primarily used in nutritive, medicinal, and cosmetic products. Previous attempts to increase the antioxidant content of sweet basil were associated with disadvantages, including ecological problems, reduced biomass yield, and increased cost. Alternatively, the current study aimed to improve selected antioxidants and biomass yield by using chitosan as an organic and cost-effective growth promoter. In this experiment, a total of four different concentrations of chitosan were applied ( 0%, 0.2%, 0.4%, and 0.6% v/v) at two different growing stages: early growth stage (GS1: 45-day-old plant), late growth stage (GS2: 65-day-old plant), and at both growth stages (known as GS3: 45 & 65-day-old plants). Results showed that plants treated with 0.4% chitosan at GS1 reached the highest chlorophyll a (4.33 mg/cm2), chlorophyll b (2.50 mg/cm2), total chlorophyll (6.84 mg/cm2), total leaf area (2234.31 cm2), total dry biomass (22.72 g per plant), total flavonoid content (33.23 mg QUE/g DE) and DPPH inhibition (92.34%) compared to other treatments. Based on the yield and phytochemical content, it is recommended to apply chitosan at 4% on the 45-day-old plant.